‘Balish’: Bahasa Inggris Dialek Pekerja Pariwisata di Kawasan Wisata Kuta Bali - Ni Luh Sutjiati Beratha; Ni Wayan Sukarini; I Made Rajeg (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
English plays an important role for workers in the tourism sector of all classes, including wholesalers, massage therapists, parking attendants, and shop assistants. Preliminary observations show that they, in general, use Balinese dialect of English or Balish. This article describes the Balish used in tourism area of Kuta, Bali, by tourism workers who have naturalized the English language by adopting several language features, especially Balinese and Indonesian, such as sentence structures, words, and expressions. The data were analyzed using The New Englishes theory and the results showed that the use of Balinese and Indonesian words in English resulted in the creation of new words, grammatical shifts, changes in word meanings, use of idioms, use of groups of verbs, and repetition of forms. Balish has adopted several grammatical features, both from Balinese and Indonesian, and it is hoped that one day it will have regular speakers so that it becomes a pidgin.